Multi-source solid waste silt curing agent as well as preparation method and application thereof
By using multi-source solid waste silt curing agent, combined with alkaline excitation reaction and gelling, the stability and strength of silt in engineering construction are solved, and efficient curing of silt and improvement of engineering performance are achieved.
Patent Information
- Application Number
- CN202510180676.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-03-21
AI Technical Summary
Due to its poor stability, easy liquefaction, difficulty in compaction, easy to absorb water and freezing in engineering construction, the foundation strength is reduced and the engineering life is shortened. The existing curing agents are not mature enough in the curing of silt.
A multi-source solid waste silt solid agent is used, which consists of basalt solid waste, waste concrete powder, slag, alkaline exciter, sodium gluconate and polypropylene fibers. The strength and stability of silt are improved through alkaline excitation reaction and gelling.
It significantly improves the strength and stability of silt, can meet the control indicators of roadbed projects such as highways, extends the service life of the project, and reduces construction costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silt solidification, and in particular to a multi-source solid waste silt solidifier and a preparation method and application thereof. Background Art
[0002] Silt is widely distributed. It is a type of soil with greatly different mechanical properties between cohesionless soil and cohesive soil. The engineering properties of silt are closely related to its formation conditions, material composition, accumulation age, geographical environment and spatial distribution law. Therefore, the properties of silt in different regions are different, but the characteristics of "silt particles" determine that they still have certain commonalities. Silt has poor stability, weak plasticity, low cohesion and high dispersibility; under dynamic load, saturated silt is prone to liquefaction; silt has uniform particle size, poor grading and is difficult to compact; the capillary water rise in silt is relatively high. In areas with high groundwater levels, the rise of capillary water will greatly reduce the strength of silt foundations and cause damage; in seasonally frozen areas, silt often has strong frost heave. Due to the unique properties of silt, it is difficult to shape it during construction when used as fill for foundation projects such as roadbeds. The compaction degree is difficult to meet the requirements, and its strength and stability cannot meet the requirements. It is also very easy to absorb water, accumulate ice and swell, and turn into slurry, which leads to cracking due to loss of foundation strength, greatly shortening the service life of the project.
[0003] In order to improve and enhance the engineering properties of silt, silt is generally reinforced by adding solidifying materials (such as cement, lime, etc.). Although many types of solidifying agents have been developed, most of them are used to reinforce clay and silt. Some simple traditional soil stabilization methods are far from meeting the technical requirements of engineering construction in silt areas. Especially in the process of transportation engineering construction, silt cannot be directly used as a filler for high-speed railway and highway roadbed. At present, the research on silt solidification is not fully mature in theory or practice. There is little research on the silt solidification and stabilization mechanism at home and abroad, which restricts the development of silt solidification technology and brings outstanding technical problems to engineering construction in silt areas. Summary of the invention
[0004] The purpose of the present invention is to provide a multi-source solid waste silt solidifier and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a multi-source solid waste silt solidifier, which comprises the following raw materials, by mass percentage: 20-30% of basalt solid waste, 5-10% of waste concrete powder, 15-25% of slag, 20-35% of alkaline activator, 5-15% of sodium gluconate and 5-10% of polypropylene fiber.
[0007] Furthermore, the multi-source solid waste silt solidifying agent comprises the following raw materials in terms of mass percentage:
[0008] Basalt solid waste 20~30%, waste concrete powder 5~10%, slag 15~20%, alkaline activator 20~30%, sodium gluconate 5~10% and polypropylene fiber 5~10%.
[0009] Furthermore, the multi-source solid waste silt solidifier includes the following raw materials, in percentage by mass: 30% basalt solid waste, 5% waste concrete powder, 20% slag, 30% alkaline activator, 10% sodium gluconate and 5% polypropylene fiber.
[0010] Furthermore, the alkaline activator is composed of water glass and calcium hydroxide;
[0011] And / or, the length of the polypropylene fiber is 7-10 mm.
[0012] Basalt is a chemical raw material. The solid waste (basalt solid waste) generated after chemical production is usually landfilled after treatment, which reduces the utilization rate of basalt solid waste and causes certain pollution to the environment. However, basalt solid waste is mainly composed of minerals such as calcium feldspar, pyroxene and albite. The microscopic particle morphology is an irregular polygon, which can provide raw materials for the alkali-induced reaction process.
[0013] Waste concrete powder is mainly composed of cement particles that have not been completely hydrated, fully hydrated cement stone, coarse and fine aggregate powder and other particles. Its chemical composition mainly includes CaO, SiO 2 and Al 2 O 3 Oxides such as CaO and SiO 2 The content of calcium components and silicon components is particularly significant, with a total content of about 66.41%, while CaO and SiO 2 They are all active oxides and can promote the hydration reaction.
[0014] The main component of slag is silicon dioxide, which generates cementitious compounds such as calcium silicate hydrate, calcium aluminate hydrate and calcium aluminosilicate hydrate under alkaline excitation and interaction with other materials, which can improve the strength and stability of silt.
[0015] Sodium gluconate is a highly efficient retarder. The composite alkali activator mixed with water glass and calcium hydroxide will make the polymerization and hydration reaction of geopolymers faster and the setting time is very short. It will cause difficulties in actual construction. Adding sodium gluconate can prolong the setting time.
[0016] Under the interaction of friction and cohesion of silt, polypropylene fiber can form a spatial network structure in silt, thereby constraining the displacement and deformation of silt particles and improving the water stability of soft soil; polypropylene fiber can also bear part of the tensile stress when the silt is deformed, thus improving the unconfined compressive strength and crack resistance of soft soil. In addition, the elastic modulus of polypropylene fiber is much larger than the rebound modulus of silt, so the rebound modulus of silt mixed with polypropylene fiber will be improved. Specifically, the use of polypropylene fiber to improve silt can improve the shear strength of the soil and make the reinforced soil show mechanical properties close to isotropic.
[0017] The third technical solution of the present invention: A method for preparing the above-mentioned multi-source solid waste silt solidifier comprises the following steps: mixing the raw materials according to a proportion to obtain the multi-source solid waste silt solidifier.
[0018] The fourth technical solution of the present invention: an application of the above-mentioned multi-source solid waste silt solidifying agent in silt solidification.
[0019] The fifth technical solution of the present invention: an application of the above-mentioned multi-source solid waste silt solidifying agent in road surface repair or roadbed reinforcement.
[0020] Technical solution 6 of the present invention: A method for solidifying silt using a multi-source solid waste silt solidifying agent, comprising the following steps:
[0021] The basalt solid waste, waste concrete powder, slag, sodium gluconate, polypropylene fiber and silt are mixed evenly, and then a solution of an alkaline activator is added, and after mixing evenly, a mixed soil sample is obtained, and the mixed soil sample is sealed and cured to obtain solidified silt;
[0022] The basalt solid waste, waste concrete powder, slag, sodium gluconate, polypropylene fiber and alkaline activator constitute the multi-source solid waste powder soil curing agent;
[0023] The multi-source solid waste silt solidifier comprises the following raw materials, measured by mass percentage: 30-50% of basalt solid waste, 20-30% of waste concrete powder, 30-50% of slag, 5-20% of alkaline activator, 5-10% of sodium gluconate and 5-10% of polypropylene fiber.
[0024] Furthermore, the amount of water used in the alkaline activator solution is the amount of water used to adjust the moisture content of the silt to 14-16%; the amount of the multi-source solid waste silt solidifying agent is 4-8% of the mass of the silt (dried silt).
[0025] Furthermore, the amount of water used in the alkaline activator solution is an amount of water used to adjust the moisture content of the silt to 15%.
[0026] Furthermore, the curing time is 7 days; the curing temperature is 20±1°C.
[0027] When multi-source solid waste silt solidifier is mixed with silt, it will react and release heat, causing the water to evaporate too quickly, resulting in the soil moisture content being lower than the optimal moisture content, thus affecting the full reaction between the materials. Therefore, temperature control is required during construction.
[0028] Furthermore, the temperature control method includes one or more of the following methods:
[0029] Method 1: Control the construction time: In the hot season, try to choose the time period of relatively low temperature in the morning and evening to carry out construction, and avoid backfilling work at noon when the sun is directly shining and the temperature is highest.
[0030] Method 2: Sprinkle water to cool down: Sprinkle water on the surface of the mixed soil sample to remove heat through evaporation of water to achieve the purpose of cooling down. However, it is necessary to control the amount of water sprayed and detect the moisture content of the mixed soil sample in real time to avoid excessive moisture affecting the performance of the solidified silt.
[0031] Method 3: Use cooling equipment: For large-scale roadbed backfill projects, consider using special cooling equipment, such as sprayers or air coolers, to cool the mixed soil samples.
[0032] Method 4, monitoring and feedback: During the construction process, a temperature sensor is installed inside the soil sample to monitor the internal temperature of the mixed soil sample in real time, and the construction plan and measures are adjusted in time according to the monitoring results.
[0033] The present invention discloses the following technical effects:
[0034] (1) The raw materials of the multi-source solid waste silt solidifying agent of the present invention are mostly derived from industrial waste, which is low in cost. In addition, compared with cement-based solidifying agents, the multi-source solid waste silt solidifying agent of the present invention has a better effect in solidifying silt and can achieve the required engineering properties (such as improving the strength and durability of the road surface, while also reducing cracking and deformation of the road surface).
[0035] (2) The silt mixed with cement or a mixture of cement and lime in the prior art has low strength, poor water stability, small cohesion and internal friction angle, and large deformation, which cannot meet the control indicators of highway and other roadbed projects. However, the silt mixed with the multi-source solid waste silt solidifying agent of the present invention has a lower degree of porosity development, increased soil density, high early strength, great potential for later strength development, good water stability, large cohesion and internal friction angle, and small deformation, which can fully meet the control indicators of highway and other roadbed projects.
[0036] (3) The existing multi-source solid waste silt solidifier, such as cement or lime, has a complicated preparation process and high economic cost. However, the component materials in the multi-source solid waste silt solidifier of the present invention are easy to purchase and low in cost. At the same time, during preparation, it is only necessary to grind each component into powder and then mix and stir it. The preparation process is simple. When solidifying the silt, it is only necessary to mix and stir the multi-source solid waste silt solidifier with the silt according to the engineering requirements. The construction process is simple. Therefore, it has good economic benefits.
[0037] (4) The multi-source solid waste silt solidifying agent of the present invention is based on basalt solid waste, which can provide raw materials for the alkali-induced reaction process. At the same time, polypropylene fibers are added to the solidifying agent. In the process of continuous connection and polymerization of the gelling material and filling of the soil pores, the polypropylene fibers are wrapped by the gelling material and overlapped with the soil particles to form a composite material with higher connection strength. The composite material is attached to the surface of the soil, which greatly improves the strength of the silt. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The “parts” described in the following examples are all “parts by mass”.
[0044] The raw materials used in the specific implementation of the present invention are as follows:
[0045] (1) Silt, basic physical properties, particle size and weight of each particle size are summarized in Tables 1 and 2.
[0046] Table 1 Basic physical properties of silt
[0047]
[0048] Table 2 Summary of silt particle size and weight of each particle size
[0049] (2) Basalt solid waste and slag. The specific composition is shown in Table 3.
[0050] Table 3 Composition of basalt solid waste and slag
[0051]
[0052] The average particle size of basalt solid waste is 74 μm, and the average particle size of slag is 74 μm.
[0053] (3) Alkaline activator, composed of water glass and calcium hydroxide in a mass ratio of 4:1.
[0054] (4) The length of polypropylene fiber is 7~10mm.
[0055] (5) The average particle size of waste concrete powder is 74 μm, and its chemical composition mainly includes CaO, SiO 2 and Al 2 O 3 The mass proportions of these oxides are 60.18%, 19.72% and 8.30% respectively, and the rest are other components.
[0056] Embodiments 1 to 9
[0057] A method for solidifying silt using a multi-source solid waste silt solidifier:
[0058] (1) The composition and proportion of the multi-source solid waste silt solidifier are shown in Table 4.
[0059] Table 4 Composition and proportion of multi-source solid waste silt solidifier
[0060]
[0061] (2) Use multi-source solid waste silt solidifier to solidify silt (the dosage of multi-source solid waste silt solidifier is 5wt.% of the silt mass):
[0062] After drying the silt, slag, basalt solid waste powder, waste concrete powder, fiber and sodium gluconate are added and mixed evenly to obtain a dry mixture.
[0063] The required amount of water is calculated based on the optimal moisture content (making the moisture content of the silt 15.8%), and the water is added to the alkaline activator and stirred until it is completely dissolved. Finally, the stirred alkaline activator solution is added to the dry mixture, mixed evenly, and a mixed soil sample is obtained.
[0064] The mixed soil samples were made into unconfined compressive strength specimens and sealed and cured for 7 days. The unconfined compressive strength was measured with reference to the "Highway Engineering Quality Inspection and Assessment Standard" JTGF801-2017. The results are shown in Table 4.
[0065] During the sealed curing period, a standard curing box is used for curing, and the temperature inside the mixed soil sample is controlled at 20±1℃ during the curing period.
[0066] Comparative Example 1
[0067] A method for solidifying silt using a silt solidifying agent:
[0068] (1) The raw materials of silt solidifier, calculated by mass percentage, are: 30% steel slag, 30% slag and 40% cement (P.O32.5R).
[0069] The specific composition of steel slag is shown in Table 5.
[0070] Table 5 Specific composition of steel slag
[0071]
[0072] (2) Use a silt solidifier to solidify the silt (the amount of the silt solidifier is 5wt.% of the silt mass):
[0073] After drying the silt, add steel slag, slag and cement, mix well to obtain a dry mixture.
[0074] The required amount of water is calculated based on the optimal moisture content (making the moisture content of the silt 15.8%), and the water is added to the dry mixture and mixed evenly to obtain a mixed soil sample.
[0075] The mixed soil samples were made into unconfined compressive strength specimens and sealed and cured for 7 days to measure the unconfined compressive strength.
[0076] During the sealed curing period, a standard curing box is used for curing, and the temperature inside the mixed soil sample is controlled at 20±1℃ during the curing period.
[0077] The unconfined compressive strength was measured to be 3.22MPa.
[0078] Comparative Example 2
[0079] A method for solidifying silt using a silt solidifying agent:
[0080] (1) The raw materials of the silt solidifying agent, calculated by mass percentage, are: 45% calcium carbide slag, 35% slag and 20% cement (P.O32.5R).
[0081] The specific composition of carbide slag is shown in Table 6.
[0082] Table 6 Specific composition of carbide slag
[0083]
[0084] (2) Use a silt solidifier to solidify the silt (the amount of the silt solidifier is 5wt.% of the silt mass):
[0085] After drying the pulverized soil, add carbide slag, slag and cement, mix well to obtain a dry mixture.
[0086] The required amount of water is calculated based on the optimal moisture content (making the moisture content of the silt 15.8%), and the water is added to the dry mixture and mixed evenly to obtain a mixed soil sample.
[0087] The mixed soil samples were made into unconfined compressive strength specimens and sealed and cured for 7 days to measure the unconfined compressive strength.
[0088] During the sealed curing period, a standard curing box is used for curing, and the temperature inside the mixed soil sample is controlled at 20±1℃ during the curing period.
[0089] The unconfined compressive strength was measured to be 2.95 MPa.
[0090] Comparative Example 3
[0091] A method for solidifying silt using a silt solidifying agent:
[0092] (1) The raw materials of silt solidifier, calculated by mass percentage, are: 60% lime and 40% cement (P.O32.5R).
[0093] (2) Use a silt solidifier to solidify the silt (the amount of the silt solidifier is 5wt.% of the silt mass):
[0094] After drying the silt, add lime and cement and mix well to obtain a dry mixture.
[0095] The required amount of water is calculated based on the optimal moisture content (making the moisture content of the silt 15.8%), and the water is added to the dry mixture and mixed evenly to obtain a mixed soil sample.
[0096] The mixed soil samples were made into unconfined compressive strength specimens and sealed and cured for 7 days to measure the unconfined compressive strength.
[0097] During the sealed curing period, a standard curing box is used for curing, and the temperature inside the mixed soil sample is controlled at 20±1℃ during the curing period.
[0098] The unconfined compressive strength was measured to be 2.56 MPa.
[0099] By comparing Examples 1 to 7 with Comparative Examples 1 to 3, it is found that the unconfined compressive strength of the silt added with the silt curing agent prepared in Examples 1, 4, 5, and 6 of the present invention is improved to varying degrees compared with Comparative Examples 1 to 3, and the silt exhibits good mechanical properties and can meet the performance requirements of the silt roadbed of the highway.
[0100] From the test results in Table 4, it can be seen that after replacing polypropylene fiber with basalt fiber and steel fiber, the strength decreases to varying degrees. The reason is that the surface of basalt fiber and steel fiber is smooth, and the fiber is wrapped by gelling material and the overlap with soil particles is not tight, so the strength decreases when it is attached to the surface of the soil. The strength decreases more when steel fiber is added, because the steel fiber is not easy to stir evenly, and there are fiber agglomeration and uneven distribution, which causes the interface bonding properties of steel fiber and other materials to deteriorate, and the uneven steel fiber bundles increase the weak layer of the interface, which makes it easy for the specimen to be damaged in the weak area of the interface when it is compressed, and finally leads to a greater decrease in the unconfined compressive strength of the specimen with steel fiber.
[0101] It can be seen from the test results in Table 4 that the optimal ratio of the comprehensive curing agent based on basalt solid waste, slag and waste concrete geopolymer provided by the present invention is: basalt solid waste: waste concrete powder: slag: alkaline activator: sodium gluconate: polypropylene fiber = 30:5:20:30:10:5. When it is used for silt solidification, the unconfined compressive strength of the silt is 4.33 MPa.
[0102] Effect Example 1
[0103] With reference to the "Highway Engineering Quality Inspection and Assessment Standard" JTGF801-2017 and the "Field Test Procedure for Dynamic Rebound Modulus of Highway Engineering Roadbed" DB34 / T 3704-2020, a multi-source solid waste silt solidifier was prepared according to the raw material ratio of Example 1, and the multi-source solid waste silt solidifier was used to solidify the powder (the specific method is the same as that in the embodiment), and then the unconfined compressive strength, compression modulus, shear strength and cohesion of different curing ages were tested. The results are shown in Table 7.
[0104] Table 7
[0105]
[0106] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A multi-source solid waste silt solidifier, characterized in that: Calculated by mass percentage, the raw materials include: 20-30% of basalt solid waste, 5-10% of waste concrete powder, 15-25% of slag, 20-35% of alkaline activator, 5-15% of sodium gluconate and 5-10% of polypropylene fiber.
2. The multi-source solid waste silt solidifier according to claim 1, characterized in that: Calculated by mass percentage, the raw materials include: 20-30% of basalt solid waste, 5-10% of waste concrete powder, 15-20% of slag, 20-30% of alkaline activator, 5-10% of sodium gluconate and 5-10% of polypropylene fiber.
3. The multi-source solid waste silt solidifying agent according to claim 1, characterized in that: Calculated by mass percentage, the raw materials include: 30% of basalt solid waste, 5% of waste concrete powder, 20% of slag, 30% of alkaline activator, 10% of sodium gluconate and 5% of polypropylene fiber.
4. The multi-source solid waste silt solidifier according to claim 1, characterized in that: The alkaline activator is composed of water glass and calcium hydroxide; And / or, the length of the polypropylene fiber is 7-10 mm.
5. A method for preparing a multi-source solid waste silt solidifier according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the raw materials according to a proportion to obtain the multi-source solid waste pulverized soil curing agent.
6. Use of the multi-source solid waste silt solidifier according to any one of claims 1 to 4 in silt solidification.
7. Use of the multi-source solid waste silt curing agent according to any one of claims 1 to 4 in pavement repair or roadbed reinforcement.
8. A method for solidifying silt using a multi-source solid waste silt solidifier, characterized in that: The following steps are involved: The basalt solid waste, waste concrete powder, slag, sodium gluconate, polypropylene fiber and silt are mixed evenly, and then a solution of an alkaline activator is added, and the mixed soil sample is obtained after mixing evenly, and the mixed soil sample is cured to obtain solidified silt; The basalt solid waste, waste concrete powder, slag, sodium gluconate, polypropylene fiber and alkaline activator constitute the multi-source solid waste powder soil curing agent; The multi-source solid waste silt solidifier comprises the following raw materials, measured by mass percentage: 20-30% of basalt solid waste, 5-10% of waste concrete powder, 15-25% of slag, 20-35% of alkaline activator, 5-15% of sodium gluconate and 5-10% of polypropylene fiber.
9. The method according to claim 8, characterized in that The amount of water used in the alkaline activator solution is the amount of water used to adjust the moisture content of the silt to 14-16%; And / or, the dosage of the multi-source solid waste silt solidifying agent is 4-8% of the mass of the silt.
10. The method according to claim 8, characterized in that The curing time is 7 days; And / or, the curing temperature is 20±1°C.
Citation Information
Patent Citations
Single-component geopolymer curing agent based on multi-element solid waste and preparation method of single-component geopolymer curing agent
CN113354310A
Basalt and glass powder geopolymer and preparation method thereof
CN116003010A
Fiber-containing early-strength tough cementing material and preparation method thereof
CN117486519A
Alkali-activated foam concrete and preparation method thereof
CN119080468A